The role of parents in educating children during online classes - Puspita, Hany Dwi (CV. Mitra Palupi, 2021)
Background: The role of parents nowadays is as a substitute for teachers at school. In order to always guide and teach assignments given by the teacher online. With parental guidance, this online learning will run well, safely, and effectively. In fact, many parents experience difficulties because they are busy working so that they cannot accompany their children directly. In addition, parents are so busy with daily routines. The role of parents, especially mothers, is now increasing, who previously only took care of the house, now have shifted to educating and accompanying their children for online learning.Purpose: This study aims to determine the perspective of parents as companions of children at home and to determine the role of parents in implementing learning at home during a pandemic.Design and methods: The method used in this research is a narrative method with a qualitative approach, with a case study type approach. This approach seeks to describe and elaborate on a complex case from various dimensions. In this case, the research analyzes the role of parents in educating their children during online classes. Learning at home makes parents find many difficulties in teaching children about the material provided by the teacher. Children usually have direct interaction with their teachers.Results: The role of parents in educating their children online is very important. When the school is face-to-face, the teacher is the one who pays attention to the students to what extent the students understand the lessons, but if online parents have to really educate, direct. Especially mom. The involvement of parents in supervising children has a very big influence on the success of children in a pandemic like this. Parents help direct children such as writing, reading, and doing their assignments. When a child cannot do his job, the mother helps him.